Anaerobic Digestion of Mixed Leaf and Petiole Waste and Food Waste in Single and Two Anaerobic Reactors - ปัญญาปิง, กลิ่นประทุม; มณีสว่าง, จุฑามาศ; บุญสิริ, นัฐญา (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The purpose of this study was to determined biogas and methane yield, including the organic removal efficiency obtained from anaerobic digestion of mixed leaf: mango, lychee, and trek and food waste mixed with the inoculum from swine farm. Four sets of experiment using single and two anaerobic reactors were performed. Each experiment was two replicates. The ratio of mixed leaf and food waste 3 : 2, the ratio of waste and inoculum 0.2 were used. The result showed that the pH values of single and two anaerobic reactors were in the range of 6.43 - 8.03, and 6.01 - 7.59, respectively. The temperatures were in the range of 25 - 35 ºC. Co-digestion in two anaerobic reactors provided the highest biogas and methane yield 144.5 L, and 104 L, respectively. Single digestion in single reactor, that was control set using only food waste in digestion, provided the lowest biogas and methane yield 120.75 L, and 14 L, respectively. The hydraulic retention time was the same in 22 days. Co-digestion in two anaerobic reactors under the neutral condition provided much more biogas and methane yield than that of the single anaerobic reactor. Besides, co-digestion in two anaerobic reactors under the neutral condition provided the highest organic removal efficiency in terms of total solids, volatile solids, and COD were 75 %, 78 %, and 82 %, respectively. In conclusion, co-digestion under neutral condition in two anaerobic reactors had the effect on biogas and methane generation more than that in the single anaerobic reactor. It is recommended to study and develop co-digestion in two anaerobic reactors using other factors, including the application for biogas production from solid organic waste.